Perlindungan terhadap Lembaga Consumer Finance atas Wanprestasi yang Dilakukan oleh Konsumen - Purwanti, Cindy Mutiara; Zulham, Zulham (Fakultas Syariah INSURI Ponorogo, 2023)
This research discusses how the law protects business actors from consumers who do not have good faith in carrying out their obligations in paying installments. So, this study aims to analyze, prove, and find value on the principle of default committed by consumers in cases between PT. SINARMAS MULTIFINANCE MEDAN BRANCH with its debtors in decision No. 688/Pdt.Sus-Bpsk/2018/PN Medan. Based on the objectives to be achieved, this study uses a normative juridical method using references from various books, journals, legislation, and other supporting literacy. The results of this study reveal that the agreement given by the consumer finance party regarding the rights and obligations imposed on the debtor is to pay instalments, if this obligation is not fulfilled then a subpoena can be given. If it is not fulfilled, then the goods that are used as objects can be withdrawn, as a result the debtor can lose the right to the goods, and the consumer finance party can terminate the agreement unilaterally. Finally, this study concludes that there has been an act of default by the debtor to the creditor. Furthermore, he found that the form of protection for consumer finance for motorized vehicles for consumer default, namely the agreement of substitution power for unit acquisition and the sale of fiduciary guarantees.